THE STUDY OF 2D THERMAL DISTRIBUTIONS USING FLUENT SIMULATION PROGRAM FOR PASSIVE SOLAR CONCEPT ' OF LOW RISE. BUILDING - MOHAMED HAMDAN, MOHAMAD FARID (Universiti Teknologi Petronas, 2008)
This report basically discusses the project research and basic understanding for one of the elements in the chosen topic, which is The Study of 2D Thermal Distributions Using Fluent Simulation Program for Passive Solar Concept of Low Rise Building. The general objective is to study the Green Building features for low rise residential building. This lead to the specific objective of the project which is to analyze the temperature distribution inside a low rise terrace house and simulate using Computational Fluid Dynamic (CFD) program in order to compare the temperature distribution pattern. The method established was using the CFD simulation program, named Gambit and Fluent, with all the parameters and conditions set to obtain the temperature distribution in 2D dimension. The Green Building features were proposed into the subject rooms by modifYing the window dimension and proposed the air chimney at the room's ceiling. The results indicate that the temperature inside the master and single bedroom was reduced when the window dimension is increased and the proposed air chimney help to ventilate the room better. The study also shown that the simulated data was reliable compare to the measured data with an error less than 1%.